ESTIMASI BIAYA PENCEGAHAN DAN PENGAWASAN K3 PADA PROYEK KONSTRUKSI - I Wayan Jawat; I Nyoman Suwitanujaya (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2018)
ABSTRACT The construction phase is a stage that needs attention so that the main goal of producing a quality project can be achieved. In the construction phase, project managers should consider the positive and negative aspects that will occur in the next stage, the operational phase. The construction project is a job sector that has high risk compared to other sectors. The number of work accidents in Indonesia is quite high and continues to increase from previous years. the number of accidents in Indonesia continues to increase from 2007 to 2011. The number of work accidents in Indonesia in 2008 experienced the highest increase of 13.17%. While in 2011 the number of work accidents in Indonesia that the smallest increase is 0.79%. It indicates the risk of accidents in Indonesia is quite high. Cost of safety can be divided by other approaches that consist of cost prevention, inspection cost, and accident cost. If the security system is not valid or there is no safety program, usually the cost of prevention and inspection is not provided or available but small (less adequate), while the accident costs are great. prevention and inspection is sufficient, so as to reduce the cost of accidents to be small. Safety and work safety management system planning is a series of steps, hazard identification, risk assessment, risk control, and cost calculation of risk control. Based on this it becomes interesting to do an assessment of the estimated cost prevention (prevention cost) and inspection cost (K3) on the construction project. The results of the review on the construction project reviewed indicate that the costs required for prevention cost and inspection cost of work accidents amount to IDR 726,182,726.28 or 5.39% of the total contract value consisting of the cost of personal protective equipment amounting to IDR 585,780,486.28, the cost of occupational safety and health equipment of IDR 32,402,240.00 and the cost of personnel of occupational safety and health is IDR 108.000.000,00. Keywords: cost estimation, construction project, risk, work accident